Electroacupuncture-Induced Muscular Inflammatory Pain Relief Was Associated With Activation of Low-Threshold Mechanoreceptor Neurons and Inhibition of Wide Dynamic Range Neurons in Spinal Dorsal Horn - Duan-Mu, Cheng-Lin; Zhang, Xiao-Ning; Shi, Hong; Su, Yang-Shuai; Wan, Hong-Ye; Wang, Yi; Qu, Zheng-Yang; He, Wei; Wang, Xiao-Yu; Jing, Xiang-Hong (Frontiers in Neuroscience, 2021)
Acupuncture is an effective alternative therapy for pain management. Evidence suggests that acupuncture relieves pain by exciting somatic afferent nerve fibers. However, the mechanism underlying the interaction between neurons in different layers of the spinal dorsal horn induced by electroacupuncture (EA) remains unclear. The aim of this study was to explore the mechanism of EA relieving inflammatory muscle pain, which was associated with activation of the spontaneous firing of low-threshold mechanoreceptor (LTM) neurons and inhibition of wide dynamic range (WDR) neuronal activities in the spinal dorsal horn of rats. Inflammatory muscle pain was induced by injecting complete Freund’s adjuvant into the right biceps femoris muscle. EA with intensity of threshold of A fibers (Ta) in Liangqiu (ST34) muscle considerably inhibited the abnormal spontaneous activities of electromyography (EMG) due to muscle inflammation. While EA with intensity of C-fiber threshold (Tc) increased the abnormal activities of EMG. EA with Ta also ameliorated the imbalance of weight-bearing behavior. A microelectrode array with 750-μm depth covering 32 channels was used to record the neuronal activities of WDR and LTM in different layers of the spinal dorsal horn. The spontaneous firing of LTM neurons was enhanced by EA-Ta, while the spontaneous firing of WDR neurons was inhibited. Moreover, EA-Ta led to a significant inverse correlation between changes in the frequency of WDR and LTM neurons (r = −0.64, p < 0.05). In conclusion, the results indicated that EA could alleviate inflammatory muscle pain, which was associated with facilitation of the spontaneous firing of LTM neurons and inhibition of WDR neuronal activities. This provides a promising evidence that EA-Ta could be applied to relieve muscular inflammatory pain in clinical practice.